2013
DOI: 10.3389/fnbeh.2013.00217
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant neural synchrony in the maternal immune activation model: using translatable measures to explore targeted interventions

Abstract: Maternal exposure to infection occurring mid-gestation produces a three-fold increase in the risk of schizophrenia in the offspring. The critical initiating factor appears to be the maternal immune activation (MIA) that follows infection. This process can be induced in rodents by exposure of pregnant dams to the viral mimic Poly I:C, which triggers an immune response that results in structural, functional, behavioral, and electrophysiological phenotypes in the adult offspring that model those seen in schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 186 publications
(259 reference statements)
1
31
1
Order By: Relevance
“…Striatal dopamine level reductions reported in Poly(I:C) MIA offspring (Ozawa et al, 2006) are sensitive to antipsychotic treatment (Zuckerman et al, 2003). Alterations to proper cortical functioning in adult offspring from Poly(I:C) MIA and neural synchrony disturbances between the Hipp and PFC, associated with schizophrenia, have been identified in the Poly(I:C) MIA animal model (Zhang et al, 2012;Dickerson & Bilkey, 2013). Compromised levels of dopamine (Bitanihirwe et al, 2010), and serotonin (Winter et al, 2009) are reported in the NAc, Hipp, and PFC and changes in levels of GABA are reported in the Hipp and Amyg (Nyffeler et al, 2006b) 2007).…”
Section: The Polyinosinic:polycytidylic Acid Model In Comparison To Omentioning
confidence: 97%
See 4 more Smart Citations
“…Striatal dopamine level reductions reported in Poly(I:C) MIA offspring (Ozawa et al, 2006) are sensitive to antipsychotic treatment (Zuckerman et al, 2003). Alterations to proper cortical functioning in adult offspring from Poly(I:C) MIA and neural synchrony disturbances between the Hipp and PFC, associated with schizophrenia, have been identified in the Poly(I:C) MIA animal model (Zhang et al, 2012;Dickerson & Bilkey, 2013). Compromised levels of dopamine (Bitanihirwe et al, 2010), and serotonin (Winter et al, 2009) are reported in the NAc, Hipp, and PFC and changes in levels of GABA are reported in the Hipp and Amyg (Nyffeler et al, 2006b) 2007).…”
Section: The Polyinosinic:polycytidylic Acid Model In Comparison To Omentioning
confidence: 97%
“…Further, acute treatment with clozapine, the first atypical antipsychotic drug available, was reported to reverse impaired long-range neural synchrony between the hippocampus and medial prefrontal cortex (mPFC), a particular functional deficit observed in the Poly(I:C) MIA rat model which is associated with the presentation of schizophrenialike behavior (Dickerson & Bilkey, 2013). The effect of clozapine on the reduced coupling between the mPFC and the hippocampus may contribute to its therapeutic effects in schizophrenia, and the Poly(I:C) MIA model may serve as a tool to investigate the molecular changes underlying the observed functional deficits, potentially leading to the exploration of novel intervention strategies targeting these molecules (Dickerson & Bilkey, 2013).…”
Section: Polyinosinic:polycytidylic Acid-assisted Maternal Immune Actmentioning
confidence: 99%
See 3 more Smart Citations